PENERAPAN METODE PEMBELAJARAN PESAWAT MASALAH UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN DI KELAS XI MIA 2 SMA ISLAM AS-SHOFA PEKANBARU - Putri Ayang Alika; Rasmiwetti '; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This is a classroom action research. This research is an attempt to improve student learning activities in chemistry on class XI MIA 2 SMA Islam As-Shofa Pekanbaru by using learning method plane problem. Student learning activity which is repaired the activity of making questions, working on plane problem, group discussion, submit answers or opinions, and enthusiastic about the game of plane problem. This research consisted of two cycles. Each cycle consisted of two meetings that went through four stages of implementation: planning, action, observation, and reflection. The collecting data used observation and test. The analysis data was describ with descriptively by using percentage technique. Based on the results obtained, it can be concluded the using of learning method plane problem can improve the activity and student learning outcomes. It can be seen by the improvement of student’s learning activity from 62,41% at the first cycle to 76,38% at the second cycle, and learning completeness from 68,96% at the first cycle to 82,75% at the second cycle.Keyword: Learning method plane problem, activities, learning outcomes